Radiocarbon Datings of Fossil Shells on Raised Beaches on the East Coast of Lutzow-Holm Bay, East Antarctica - Kiichi MORIWAKI (National Institute of Polar Research, 1974)
An investigation was conducted during the austral summer, Jan.-Feb., 1972, at the east coast Liitzow-Holm Bay, Antarctica. Two kinds of fossil shells (Adamussium colbecki and Laternula elliptica) were collected for radiocarbon dating at four localities on raised beaches of the northern part of the Lang Hovde district. Altitudes of sampling localities are 1.5m, 5-6 m, 6m± and 6m± above sea level, and radiocarbon dates of samples are 4,290 ±90, 23,830 ±910, 10,250±210 and over 33,400 years before present, respectively. These data together with the results obtained by Y. YOSHIDA (1971) are plotted on a time-altitude graph. Relationship between time (age) and altitude is not yet elucidated completely in connection with the eustatic change of sea level and the crustal uplift. The fact that the older levels seem to correspond to higher beaches and the younger to the lower, however, may suggest that the region was uplifted isostatically. Though it is not clear whether the uplift was continuous or intermittent, the graph indicates at least the composite effect of eustatic and isostatic movements in the region. From the graph it may be safely said that the high stands of sea level relative to land must have existed about 4,000 years B. P., 24,000 years B. P. and 30,000 or more years B. P. It may be said that these levels correspond roughly to warm stages interpreted by the analysis of ice core samples obtained from the deep drilling at Byrd Station (EPSTEIN et al., 1971): Especially, the levels of 30,000 years B. P. and 4,000 years B. P. seem to correspond to the obvious eustatic changes of sea level. The high stand of sea level at 10,000 years B. P. commenced somewhat early in comparison with the stage of worldwide postglacial rise of sea level. If the account of a rapid rise of temperature during 17,000 and 9,000 years B. P. and of little rise of temperature since 10,000 years B. P. (DANSGAARD et al., 1969) is taken into consideration, the level of 10,000 years B. P. may be interpreted as a forerunner of the level of ...